DISTANCE AND BLENDED EDUCATION: PROBLEMS AND NEEDS OF TEACHERS DURING THE WAR - Ivaniuk , Iryna (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2023)
The article considers the problems and needs of teachers during the organization of distance and blended learning in the conditions of war. The paper presents the results of the online survey «Readiness and needs of teachers regarding the use of digital tools and ICT in war conditions: 2023», which was conducted by the Institute of Digitalization of Education of the National Academy of Pedagogical Sciences of Ukraine in March - April 2023. It was noted that during the war distance education faced new problems and challenges: the organization of distance education during widespread power outages and constant air raids; organization of the educational process for children of internally displaced persons and children who are abroad during the war; organization of distance education in educational institutions that are destroyed, partially damaged during the war, or located in temporarily occupied territory.